HUBUNGAN PELAKSANAAN PENILAIAN PRESTASI DENGAN LOYALITAS KERJA KARYAWAN PADA HOTEL RATU MAYANG GARDEN PEKANBARU - Diova Tary; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The problems that arise in this study assumed are the low employee’s loyalty at the Ratu Mayang Garden Hotel Pekanbaru showed the turnover absenteeism that fluktuatif. The problems be important because could become threat to objectif of vision and mission of the Ratu Mayang Garden Hotel . It should be solved immediately.This research aims to know how is the description about performance appraisal and the description of employee’s loyalty and how is the impact of performance appraisal towards employee loyalty at the Ratu Mayang Garden Hotel Pekanbaru.In this research methodology used is quantitative descriptive correlational techniques which were collected through questionnaire method against 91 respondents, where samples used were employees of the Ratu Mayang Garden Hotel Pekanbaru and as a source of information is the Human Resource Manager. To determine the sample using purposive sampling method. Data collection through interviews and questionnaires.Results of research and hypothesis testing showed that there is a significant positive correlation between the implementation of performance appraisal of the employee's loyalty Ratu Mayang Garden Hotel Pekanbaru. Through the Spearman rank correlation analysis known that relationship Performance Assessment of the Employee Loyalty has a coefficient 0.505 where in the interpretation of the correlation coefficient value indicates there is a relationship between the Implementation of Performance Assessment of the Employee Loyalty categorized as moderate.Keywords : Job Performance Assessment, Loyalty, Ratu Mayang Garden Hotel